Detection of far-red IRSL from loess - Lai, Z. P.; Arnold, L.; Stokes, S.; Bailey, R.; Fattahi, M. (Ancient TL, 2002)
It has recently been proposed that it may be possible to extend the age range of luminescence dating of loess using the far-red (λ=665-740nm) emission from feldspar, as it is thought not to exhibit anomalous fading. Studies on red luminescence have been hindered due to technical difficulties in suppression of background and other factors. Recently modifications to apparatus (esp. photo-multiplier plus filter combinations) have been reported demonstrating that red IRSL (λ=590-700nm) may be observed from coarse-grained feldspar (Fattahi and Stokes, 2002a). However, this modified system was not able to detect far-red IRSL (λ=665-740nm) from old (>800ka) Chinese loess. In this short note we describe further modifications to the system which have successfully enhanced the far-red IRSL signal, and at the same time reduced background signal levels. As a result, routine measurements of far-red IRSL from loess are possible.